Novel aspects of biochemical assessment of bone remodeling and mineralization - Leszczyńska, Dorota; Szatko, Alicja; Toboła, Agata; Karoń, Katarzyna; Misiorowski, Waldemar; Glinicki, Piotr; Zgliczyński, Wojciech (Frontiers in Endocrinology, 2025)
The maintenance of skeletal integrity relies on bone remodeling, a dynamic process orchestrated by the interplay between osteoclasts, osteoblasts, and the regulatory network of osteocytes. Traditional bone turnover markers (BTM) provide a non-invasive tool to assess bone metabolic activity. However, their clinical utility is limited by a low specificity and poor reproducibility. Moreover, traditional BTM do not reflect osteocyte function, despite the central role of these cells in bone remodeling. Novel BTM, including proteins (namely sclerostin, DKK-1, RANKL/OPG, and periostin), lipids (namely sphingosine-1-phosphate), and miRNAs, offer more specific insights into the interactions between bone cells and molecular signaling within the bone microenvironment. These markers represent potential therapeutic targets, with anti-sclerostin antibodies already approved for osteoporosis treatment. Another fundamental aspect of skeletal integrity is the process of mineralization, which is tightly regulated by three hormones: parathyroid hormone (PTH), vitamin D, and fibroblast growth factor 23 (FGF-23). These hormones not only maintain systemic calcium-phosphate homeostasis but also exert direct effects on bone cells, thereby influencing bone remodeling. This narrative review summarizes the functions, commonly used analytical methods, and clinical applications of novel BTM. It also presents the mechanisms of action of these hormones on bone tissue, along with new analytical approaches for measuring vitamin D, PTH, and FGF-23. The application of “omics” techniques in bone remodeling assessment is also discussed, with an emphasis on the advantages and limitations of these approaches.